Effect of an Impermeant Arginine-Modifying Reagent on the Responses of Rabbit Platelets to Agonists - Anderson, Esther R; Au-Young, Yum-Kin; Foulks, James G (Thrombosis and Haemostasis, 1983)
The importance of surface arginyl residues in platelet aggregation was investigated by studying the effects of an impermeant arginine-modifying reagent, p-sulfonylphenylglyoxal (PSPG), on platelet responses to various agonists. Pretreatment of resuspended rabbit platelets with 2-15 mM PSPG resulted in complete inhibition of aggregation responses to ADP and 5-HT, and a concentration-dependent inhibition of the preceding shape change. Aggregation responses to thrombin also were inhibited in a concentration-dependent manner. The protective effects of antagonists of these three agonists (P, y-methylene ATP forADP, hirudin for thrombin and phentolamine for 5-HT) during pretreatment of platelets with PSPG indicated that intact arginine residues form part of the receptor sites for ADP and for thrombin. Arginine residues are not part of the 5-HT receptor site itself, but seem to be important for the maintenance of the functional integrity of this site.
Keywords: Platelets; Aggregation; Arginine-modification